THE IMPORTANCE OF COMPANY OWNERSHIP AND BUSINESS TRANSACTION DATA INTEGRATION IN SUPPORTING THE EFFORTS TO PREVENT AND ERADICATE CORRUPTION IN INDONESIA - Budi Saiful Haris (Asia Pacific Fraud Journal, 2016)
Corruption is commonly committed by leaving no official trace. In disclosing big corruption cases, investigators are often challenged by defendant who always seeks to make an alibi on the charges of the investigators such as by creating fake or underlying business. The application of the principle of shifting burden of proof by the defendant could actually be detrimental to the prosecution process if the public prosecutor fail to prove to the contrary on the argument or evidence submitted by the defendant who is trying to deny the charge of public prosecutor. Such condition may occur due to the possibility that the defendant could convey some evidence of business transactions and sources of information that might not be successfully acquired by the public prosecutor, law enforcers and other relevant government agencies prior to the prosecution process. In this case, there is a big possibility that the perpetrators have manipulated financial transaction information assisted by the gatekeepers. The following entries parse the root of the problem for the matter and provide recommendations for the integration of business transparency approach to prevent and eradicate corruption by making breakthroughs that could prevent from the usage of fake financial transaction information as the evidence that could obscure the crime of corruption.